BIBLIOMETRIC ANALYSIS OF THE RESEARCH IN THE FIELD OF ACCOUNTING IN RELATION TO SUSTAINABILITY AND INTEGRATED REPORTING (Third Sector Social Economic Review, 2025)
This study examines the progression of publications on integrated and sustainability reporting within accounting field, seeking to offer a thorough overview of global trends and contributions. The study aims to identify the main authors, journals, countries, and relevant research topics, as well as to highlight possible future research directions. To achieve these goals, a bibliometric study was conducted utilising the Web of Science (WoS) database, covering 3066 documents published from 1998 to 2025 to attain these objectives. The keywords in the WoS database were “integrated reporting”, “sustainability reporting” and “accounting”. Performance analysis and bibliometric mapping approaches were applied to evaluate the retrieved data. Tools such as VOSviewer and Microsoft Excel were employed to generate visual knowledge maps, tables, and graphs for deeper insights. The results reveal a growing trend in accounting research toward sustainability and integrated reporting, in accounting research. The year 2024 demonstrates the highest number of publications with 469 publications. According to the results of the analysis, business finance, management, and environmental studies. Key themes identified include “sustainability reporting” “sustainability” and “integrated reporting”. The most cited studies, authors, and institutions were also identified, with Australia, the UK, and Italy leading in citations. The findings underline the interdisciplinary nature of sustainability reporting and its growing importance in accounting. This study provides a strong foundation for future research and enriches the literature in the field of sustainability accounting, while also providing recommendations for future research. Given the evolving nature of sustainability reporting and integrated reporting, it is suggested that studies can be conducted within the scope of technology and digitalization, corporate governance and integrated reporting, regional and sectoral studies.
Keywords: Bibliometric Analysis; Integrated Reporting; Sustainability Reporting; Accounting Research